ESPoll: Advance & Efficient Tolling System / Muhammad Farez Amirul Khairulhisham - Khairulhisham, Muhammad Farez Amirul (2024)
An effective toll system is essential for a country's transportation infrastructure because it provides the funds necessary for constructing and maintaining the highways in general. However, current tolling system mainly in Malaysia have problems such as non-standardize payment system since there are inconsistent of transaction such as used of smart cards, Radio Frequency Identification (RFiD) and currently debit card for cashless transactions at toll plazas. The inconsistency can cause traffic congestion at toll plaza itself. Furthermore, the needs of user to utilize external device is problematic since user must purchase and register the payment device. This study presents Automatic License Plate Recognition (ALPR) at toll plaza as solution using ESP32 microcontroller to control tolling system and webcam on computer to capture license plate. The study utilizes Proteus 8 software by constructing the circuitry for Printed Circuit Board (PCB) and simulate the system virtually. Moreover, this study utilizes multiple Integrated Development Environment (IDE) such as PlatformIO for embedded system development and PyCharm for ALPR processing. The input for this system consists of camera to capture license plates and infrared sensor to detect the vehicle. Meanwhile, the output is Liquid Crystal Display (LCD) for information display, servo motor for control barrier, and Neo-pixel LED for lane conditioning. The problems brought on by a lack of standardization can be solved by implementing the proposed system. However, it might be challenging to accurately capture license plates with cameras. Thus, adding QR-code based payment as a backup option in the future greatly improves the system's overall effectiveness